Physical activity outside of structured therapy during inpatient spinal cord injury rehabilitation. Issue 1 (December 2016) - Zbogar, Dominik; Eng, Janice; Miller, William; Krassioukov, Andrei; Verrier, Mary
Abstract Background Little information exists on the content of inpatient rehabilitation stay when individuals with spinal cord injury (SCI) are not engaged in structured rehabilitation therapy sessions. Investigation of inpatient therapy content is incomplete without the context of activities outside of this time. We sought to quantify physical activity occurring outside of physical therapy (PT) and occupational therapy (OT) sessions during inpatient SCI rehabilitation and examine how this activity changes over time from admission to discharge. Methods In this longitudinal observational study at two inpatient SCI rehabilitation centres, 95 participants were recruited through consecutive admissions. Physical activity at admission and discharge was recorded by 1) self-report (PARA-SCI questionnaire) and 2) real-time accelerometers worn on the dominant wrist, and hip if ambulatory. For analyses, we separated participants into those with paraplegia or tetraplegia, and a subgroup of those ambulatory at discharge. Wilcoxon signed rank tests (admission vs. discharge) were used for PARA-SCI minutes and accelerometry activity kilocounts. Results There was no change in self-report physical activity, where the majority of time was spent in leisure time sedentary activity (~4 h) and leisure time physical activity at a higher intensity had a median value of 0 min. In contrast, significant increases in physical activity outside PT and OT sessions from admission to discharge were found for wrist accelerometers for individuals with tetraplegia (i.e., upper limb activity) and hip accelerometers for ambulatory individuals (i.e., walking activity). Conclusion Physical activity is low in the inpatient SCI rehabilitation setting outside of structured therapy with a substantial amount of time spent in leisure time sedentary activity. Individuals appear to have the capacity to increase their levels of physical activity over the inpatient stay.